2022
DOI: 10.3390/ijms231810343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Global and Specific DNA-Binding Proteins on Transcriptional Regulation of the E. coli bgl Operon

Abstract: Using reporter gene (lacZ) transcriptional fusions, we examined the transcriptional dependencies of the bgl promoter (Pbgl) and the entire operon regulatory region (Pbgl-bglG) on eight transcription factors as well as the inducer, salicin, and an IS5 insertion upstream of Pbgl. Crp-cAMP is the primary activator of both Pbgl and the bgl operon, while H-NS is a strong dominant operon repressor but only a weak repressor of Pbgl. H-NS may exert its repressive effect by looping the DNA at two binding sites. StpA is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 88 publications
2
12
0
Order By: Relevance
“…Our previous results have shown that H-NS and H-NSL30P are able to bind to the bgl promoter region in the absence of bglG , while H-NSL30P even showed a higher binding affinity [39] . Here, we further demonstrated H-NS binding to its downstream site within bglG , using the lacIQ promoter driving expression of the bglG - lacZ transcriptional fusion at the lac locus (Iq-G_Z).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Our previous results have shown that H-NS and H-NSL30P are able to bind to the bgl promoter region in the absence of bglG , while H-NSL30P even showed a higher binding affinity [39] . Here, we further demonstrated H-NS binding to its downstream site within bglG , using the lacIQ promoter driving expression of the bglG - lacZ transcriptional fusion at the lac locus (Iq-G_Z).…”
Section: Resultsmentioning
confidence: 90%
“…In an earlier paper, we proposed that H-NS represses the bgl operon by forming a DNA loop between its two binding sites [39] . Here, we investigated this proposed DNA-looping mechanism in-depth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations